Conscientious objection to abortion provision: Why context matters. Issue 5 (4th May 2018) - Harris, Laura Florence; Halpern, Jodi; Prata, Ndola; Chavkin, Wendy; Gerdts, Caitlin
ABSTRACT: Conscientious objection to abortion – a clinician's refusal to perform abortions because of moral or religious beliefs – is a limited right, intended to protect clinicians' convictions while maintaining abortion access. This paper argues that conscientious objection policies and debates around the world generally do not take into account the social, political, and economic pressures that profoundly influence clinicians who must decide whether to claim objector status. Lack of clarity about abortion policies, high workload, low pay, and stigma towards abortion providers can discourage abortion provision. As the only legal way to refuse to provide abortions that are permitted by law, conscientious objection can become a safety valve for clinicians under pressure and may be claimed by clinicians who do not have moral or religious objections. Social factors including stigma also shape how stakeholders and policy-makers approach conscientious objection. To appropriately limit the scope of conscientious objection and make protection of conscience more meaningful, more information is needed about how conscientious objection is practised. Additionally, abortion trainings should include information about conscientious objection and its limits, reproductive rights, and creating an enabling environment for abortion provision. Policy-makers and all stakeholders should also focus on creating an enabling environment and reducing stigma.